2021
DOI: 10.1097/md.0000000000027796
|View full text |Cite
|
Sign up to set email alerts
|

Secondary synovial chondromatosis of the subacromial subdeltoid bursa with coexisting glenohumeral osteoarthritis

Abstract: Rationale: Synovial chondromatosis of the shoulder joint is uncommon; this condition usually affects the knee joint and the hip joint. Lesions of multiple chondral nodules form in the synovium and are usually found within the joint capsule. Treatment of synovial chondromatosis consists of loose body removal and synovectomy. In synovial chondromatosis of the shoulder, arthroscopic loose body removal and synovectomy have been reported with good outcomes. Arthroplasty can be a treatment option when osteoarthritis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Kamineni et al [12] and Shpitzer et al [13] reported that there was no difference in recurrence rate between patients treated by loose body removal alone and those treated by loose body removal with additional synovectomy. On the other hand, Lee et al [14] proposed that synovectomy to the extent possible should be performed regardless of histopathological characteristic and/or Milgram classification. To date, however, there has been no report on the long-term results of SCM of the shoulder.…”
Section: Discussionmentioning
confidence: 99%
“…Kamineni et al [12] and Shpitzer et al [13] reported that there was no difference in recurrence rate between patients treated by loose body removal alone and those treated by loose body removal with additional synovectomy. On the other hand, Lee et al [14] proposed that synovectomy to the extent possible should be performed regardless of histopathological characteristic and/or Milgram classification. To date, however, there has been no report on the long-term results of SCM of the shoulder.…”
Section: Discussionmentioning
confidence: 99%